2017
DOI: 10.1080/09593330.2017.1309078
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of the anammox process at decreasing temperatures and long SRTs

Abstract: The implementation of autotrophic nitrogen removal in the mainstream of a municipal wastewater treatment plant is currently pursued. Among the crucial unknown factors are the kinetic properties of anaerobic ammonium oxidising (anammox) bacteria at low temperatures. In this study we investigated the adaptation of a fast-growing anammox culture to a lower temperature. In a membrane bioreactor a highly enriched anammox community was obtained at 30°C, 25°C and 20°C. This culture was exposed to long-and short-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 46 publications
4
24
1
Order By: Relevance
“…A study by Lotti et al [31] reported that the highest growth rate can be found at 30 • C, and the biomass was mostly occupied by "Candidatus Brocadia sp. ", which is similar to findings in the mainstream PN/A step-feed activated sludge system operated in the Changi Water Reclamation Plant, Singapore [12] and in anammox membrane bioreactors operated at full scale in Rotterdam [57].…”
Section: Temperaturesupporting
confidence: 86%
See 1 more Smart Citation
“…A study by Lotti et al [31] reported that the highest growth rate can be found at 30 • C, and the biomass was mostly occupied by "Candidatus Brocadia sp. ", which is similar to findings in the mainstream PN/A step-feed activated sludge system operated in the Changi Water Reclamation Plant, Singapore [12] and in anammox membrane bioreactors operated at full scale in Rotterdam [57].…”
Section: Temperaturesupporting
confidence: 86%
“…The solid retention time in the operational anammox process also plays an important role because it can affect specific anammox activity when the non-active and non-anammox cells in the reactor increased therein. Therefore, temperature control in the system should be considered with respect to solid retention time [57]. The operation of anammox membrane bioreactors at 37 • C, fed with low-ammonium influent (100 mg-N/L), achieved high biomass and a high nitrogen removal rate compared to those at the same temperature but operated with an influent with higher ammonium content [8,68].…”
Section: Temperaturementioning
confidence: 99%
“…The average SA max AMX (20°C) during the described reactor run was 70 mgN (gVSS d) −1 . Other values reported in literature are diverse: SA max AMX 68.8 mgN (gVSS d) −1 (20°C enriched anammox reactor) [40], SA amx 600 mgN (gVSS d) −1 (20°C enriched anammox reactor) [41], SA max AMX 50 mgN (gVSS d) −1 (15°C PN/A reactor) [16] and SA max AMX 13.5 mgN (gTSS d) −1 (20°C PN/ A reactor) [42]. The general conclusion is that the order of magnitude of the anammox activity that can be maintained in this system is in a similar range as the reported values in the literature.…”
Section: Ammonium Conversionmentioning
confidence: 99%
“…On the other hand, in order to quantify the direct effect of temperature on the anammox activities, we consider an Arrhenius type model (Lotti et al ., 2015; Zhu et al ., 2017; Hoekstra et al ., 2018). The activation energy was considered equal to Ea = 239 kJ mol −1 consistent with the value estimated by Hoekstra et al .…”
Section: The Impact Of Global Coolingmentioning
confidence: 99%
“…The activation energy was considered equal to Ea = 239 kJ mol −1 consistent with the value estimated by Hoekstra et al . (2018). This parameterization, in particular, allows us to estimate changes in anammox activity associated with long-term temperature fluctuations, a condition that makes it ideal for exploring a scenario such as ours.…”
Section: The Impact Of Global Coolingmentioning
confidence: 99%